STUDYING THE STRUCTURE OF VAGINAL MICROBIOMA IN HEALTHY COWS AND PURULAR - CATARAL ENDOMETRITIS COWS - Radojičić, B.; Kakishev, M. G.; Gabdullin, D. E.; Muldagaliev, M. Kh. (Ғылым және білім №1, 2020)
The article presents data on the study of the microbial etiology of purulent-catarrhal endometritis at Agrofirm Akas LLP using the PCR method. In dairy enterprises, cow infertility is recorded in 20-26% of the population and often leads to significant economic damage. Among the causes of cow infertility, a special place is occupied by diseases of the reproductive system. Diseases of the organs of the reproductive system are registered in 30-51% of infertile cows and in 13-28% of heifers, and the technology of keeping dairy cows contributes to the increasing role of these diseases in the etiology of infertility. The main predisposing reasons for the occurrence of low fertility are the following factors: a decrease in the body's resistance against metabolic disorders, as well as some infectious diseases that have an indirect effect through the immune status of highly productive cows or even a direct effect on fertilization, pregnancy and the postpartum period. For example, such as Leptospirosis, Brucella or Neospora causing abortions and, consequently, reducing milk production in herds and sometimes fertility. Studies have shown that the vagina in the microflora of healthy cows is dominated by L. sakei. and W. koreensis, while there are no dominant bacterial strains in cows with endometritis in which an increase in the number of bacteria was detected. This suggests that a violation of the microflora of the vaginal microbial community can contribute to the occurrence of endometritis.В статье приведены данные по изучению микробной этиологии гнойно-катарального эндометрита в ТОО «Агрофирме Акас» с применением метода ПЦР. В условиях молочных предприятиях бесплодие коров регистрируется у 20-26% поголовья и часто приводит к значительному экономическому ущербу. Среди причин бесплодия коров особое место занимают заболевания половой системы. Болезни органов половой системы регистрируются у 30-51% бесплодных коров и у 13-28% телок, а технология содержания молочных коров способствует возрастанию роли этих заболеваний в этиологии бесплодия. Основными предраспологающими причинами для возникновения низкой оплодотворяемости оносятся следующие факторы: снижение резистентности организма на фоне нарушения метаболизма, а также некоторые инфекционные заболевания оказывающие косвенное воздействие посредством иммунного статуса у высокопродуктивных коров или даже прямого воздействия на оплодотворение, течение беременности и послеродового периода. Например такие как Leptospirosis, Brucella или Neospora вызывающие аборты и, следовательно, уменьшающие выработку молока у стад и иногда плодовитость. Исследования показали, что влагалище в микрофлоре здоровых коров преобладает L. sakei. и W. koreensis, при этом нет доминирующих бактериальных штаммов у коров с эндометритом, у которых было обнаружено увеличение количества бактерий. Это говорит о том, что нарушение микрофлоры влагалищного микробного сообщество может способствовать возникновению эндометрита.
Keywords: журнал кксон; рк; научный журнал; периодическое издание; отечественное издание; ветеринария; безплодие коров; эндометрит